International diversity and networks in collaborative research: how is the accounting academy playing the publication game? - Lourenço, I.; Renato azevedo; Oliveira, J.; Branco, M. (The Seventh International Conference of the Journal of International Accounting Research, Quebec, 2019)
This study analyses the pattern of internationalization of the accounting top journals, based on the country of affiliation of the authors of each paper. The empirical study has been composed with 3,262 papers published in 18 accounting top journals between 2013 and 2017, which were classified as National (with authors from universities belonging to the same country) and International (with authors from universities belonging to different countries). For the international papers we perform a social network analysis in which the nodes are the countries and the links are the co-authorships. Overall, the findings show that the patterns of geographical distribution of the national and international papers published in the accounting top journals vary across different groups of journals. This study extends prior literature by applying social network analysis based on the country of affiliation of the authors, rather than on the most prolific authors and their research networks.